Conflict Related Sexual Violence: Patriarchy's Bugle Call - Medawatte, Danushka (Georgetown University, 2020)
In this paper, it is argued that conflict related sexual violence is a product of patriarchy. Within that core argument, the author presents a feminist critique of the existing law pertaining to conflict related sexual violence and moves on to building a narrative of CRSV as a deliberate strategy of war.
Keywords: Sexual Violence; Gender Based Violence; Feminism; Patriarchy; Public International Law; International Humanitarian Law; International Criminal Law; Geneva Conventions; Gender; Violence; War Crimes; Intersectionalities; Inequality; Prosecutions